1.THE INTERSTITIUM (THE PRE-LYMPHATIC REGION), IS IT A NEWFOUND 'ORGAN' (Iraqi Journal of Medical Sciences, 2019)
Many of the human anatomists wouldn't expect to discover a new body part, however, researchers claim that they found a network of fluid-filled spaces in connective tissues all over the body that hadn't been seen before and it acts like an "open, fluid-filled highway" that is supported by a lattice of thick collagen "bundles". The researchers stated that tissue fixation during the procedure of histological tissue processing causes collapse of this network of fluid-filled spaces, and these spaces were not seen during light microscopic examination till the new imaging technique were developed to allow examination of living tissues on a microscopic level.Keywords: Interstitium, anatomy, neworgan, cancerCitation: Mubarak HJ. The Interstitium (the pre-lymphatic region), is it a newfound 'organ'. Iraqi JMS. 2018; 16(3): 230-231. doi: 10.22578/IJMS.16.3.1
Keywords: Interstitium; anatomy; neworgan; cancer